Democracy, violence and insecurity: Perversion and implications on the youth in Northern Nigeria - Abbo, Usman; Mohd Zain, Zawiyah (2020)
Nigeria as it is constituted today depict a picture typical of a semi-democratic entity that is undergoing a demographic transition process, where the large fraction of the total population is represented by youth with high propensity for violence. Achieving political stability in the country, therefore revolve around the existence of a workable democracy which can improve government performance and thus reduce the sources of grievances capable of generating anti-government violence by the youth. However, it is the conception of this paper that, in Nigeria the political and the socio-economic principles associated with the liberal democracy are either weakly internalized or remained largely not internalized across the body polity thereby creating room for grievance hence the persistent incidence of violence, as democracy fails to deliver its promises of good governance and economic stability. Such violence therefore interacts perversely with democratic institutions, eroding their legitimacy and effectiveness thereby engendering insecurity. Living in the midst of violence and insecurity thus transforms the youth’s perceptions of their physical and political environments which invariably weaken their commitment to democracy and encourage them to support forms of authority from nonstate actors such as Boko Haram in the North-Eastern geo-political zone and bodies of organized crime perpetrators who specialized in cattle rustling, kidnapping and banditry in the North-West geo-political zone.